Factors Affecting Taxpayer Compliance In Paying Motor Vehicle Tax (Pkb) At Samsat Bengkulu City - Aprila, Izra Putri; Nasution, Suswati; Hidayah, Nenden Restu (Journal of Management, Economic, and Accounting, 2025)
The type of research used in this research is explanatory research. The aim of this research is to determine the effect of taxpayer income on taxpayer compliance in paying motor vehicle tax (PKB) in the Bengkulu City Samsat. The results of the research show that there is an influence of income (X1) on taxpayer compliance (Y) based on the results of the tcount test for the awareness variable (X2) which is 2.455, the tcount value when compared with ttable of 1.653 and tcount>ttable (2.455>1.653) with significant level is 0.001<0.05 then Ho is rejected and Ha is accepted. There is an influence of awareness (X2) on taxpayer compliance (Y) based on the results The tcount test for the awareness variable (X2) is 2.589. If the tcount value is compared with ttable of 1.653 and tcount>ttable (2.589>1.653) with a significant level of 0.003<0.05 then Ha is rejected and Ho is accepted. There is an influence on service quality (X3 ) towards taxpayer compliance (Y) based on the results of the t-count test for the awareness variable (X2) is 3.763, the t-count value If compared with ttable of 1.653 and tcount>ttable (3.763>1.653) with a significance level of 0.002<0.05 then Ha is rejected and Ho is accepted. The Ftable result is 2.95 because Fcount>Ftable (7.894>2.65) then Ha is accepted and Ho is rejected, meaning that the variables income (X1), awareness (X2) and service quality (X3) have a significant effect simultaneously or simultaneously on taxpayer compliance ( Y) The termination coefficient value of Adjusted R Square R2= 0.780. This value means that the independent variables together contribute 78% in influencing the dependent variable with medium criteria.